Ferrocement encased lightweight aerated concrete : a novel approach to produce sandwich composite - Memon, Noor Ahmed (Elsevier, Amsterdam, 2007)
This paper presents the experimental study to investigate the applicability of a novel technique to produce lightweight sandwich composite elements. Sandwich composite is fabricated by encasing lightweight aerated concrete as core with high performance ferrocement box as skin layer. The performance of the sandwich elements is investigated in terms of ultimate compressive strength, flexural strength, water absorption, overall unit weight and the failure mode. The results are compared with control specimens made solely of the aerated concrete. Results showed the remarkable enhancement in the compressive strength and flexural strength while the water absorption is reduced to fractions as compared to that of the control specimens. Overall unit weight of the sandwich composite elements falls in the range of the lightweight structural elements. The failure mode of the sandwich elements reveals the ductile and composite behavior thus transforming a pure brittle material (aerated concrete) into ductile composite material because of the ferrocement encasement.